ℐ𝒦-Convergence in the Topology Induced by Random 2-Normed Spaces. (16th July 2013) - Yamancı, U.; Gürdal, M.
Abstract : We study ℐ 𝒦 -convergence which is common generalization of the ℐ * -convergence of sequences in the topology induced by random 2-normed spaces and prove some important results.